YAP enhances mitochondrial OXPHOS in tumor-infiltrating Treg through upregulating Lars2 on stiff matrix - Hui Li; Yuan Yao; Yang Qu; Yihan Xu; Peng Jin; Yuhan Zhang; Liling Niu; Jingchao Bai; Meinan Yan; Youhui Wang (Journal for ImmunoTherapy of Cancer)
Background Tumor-infiltrating regulatory T cells (TI-Tregs) are well-adapted to thrive in the challenging tumor microenvironment (TME) by undergoing metabolic reprogramming, notably shifting from glycolysis to mitochondrial oxidative phosphorylation (OXPHOS) for energy production. The extracellular matrix is an important component of the TME, contributing to the regulation of both tumor and immune cell metabolism patterns by activating mechanosensors such as YAP. Whether YAP plays a part in regulating TI-Treg mitochondrial function and the underlying mechanisms are yet to be elucidated.Methods To gain insights into the effect of matrix stiffness on YAP activation in Tregs, alterations in stiffness were performed both in vitro and in vivo. YAP conditional knockout mice were used to determine the role of YAP in TI-Tregs. RNA-seq, quantitative PCR, flow cytometry, lentivirus infection and mitochondrial function assay were employed to uncover the mechanism of YAP modulating mitochondrial function in TI-Tregs. A YAP inhibitor and a low leucine diet were applied to tumor-bearing mice to seek the potential antitumor strategy.Results In this study, we found that YAP, as a mechanotransducer, was activated by matrix stiffness in TI-Tregs. A deficiency in YAP significantly hindered the immunosuppressive capability of TI-Tregs by disrupting mitochondrial function. Mechanically, YAP enhanced mitochondrial OXPHOS by upregulating the transcription of Lars2 (Leucyl-tRNA synthetase 2, mitochondrial), which was essential for mitochondrial protein translation in TI-Tregs. Since Lars2 relied much on its substrate amino acid, leucine, the combination of a low leucine diet and YAP inhibitor synergistically induced mitochondrial dysfunction in TI-Tregs, ultimately restraining tumor growth.Conclusions This finding uncovered a new understanding of how YAP shapes mitochondrial function in TI-Tregs in response to mechanical signals within the TME, making the combined strategy of traditional medicine and diet adjustment a promising approach for tumor therapy.